Research Brief #5: Integrating Agriculture and Nutrition Actions to Improve Maternal and Child Nutrition: Metrics for Coordinated Research. - Webb, Patrick, 1959- (Tufts University. Tisch Library., 2016)
This briefing covers a list of questions needing to be answered by researchers from various fields surrounding Agriculture and Nutrition. The briefing also offers challenges and opportunities for research topics. Keywords: CRSP, Research Brief, Coordinated Research.